(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Political representation of women is seen as an important factor in all aspects of progresshowever India’s policies on gender equality continue to be scrutinized. After independence in 1947, anumber of measures were undertaken to strengthen women’s political presence in the numerous localgovernment structures in India through decentralizing authority. The Panchayati Raj Institutions hasenhanced the involvement in decision-making role in policy institutions by disadvantaged sectors ofsociety, including women. Therefore, by the application of quality approaches, such as paper analyses ofthe amendment act of the Panchayati Raj institutions and expert interviews with electing womanmembers of a single Keralan district, this research seeks to examine women’s political leadership withinthe local government institutions. This paper aims to recognize the problems facing women in roles ofpolitical leadership in India, the largest democratic country. Study findings show that significantprogress is being made in the role of leadership on women’s empowerment but that there are still somekey barriers to women being involved in the policy sphere.